Personality Predictors of the Attitude to the Digitalization of Education among Russian Students - D.V. Kashirskiy; N.V. Sabelnikova (Moscow State University of Psychology and Education, 2024)
The empirical study explores students’ attitudes towards digital educational technologies and the digitalization of the education system as a whole. The survey, conducted between January and April 2022, shortly after the end of the lockdown, involved students from Russian universities aged from 18 to 38 ( ). The “Attitude towards Digitalization” questionnaire (D.V. Kashirsky, A.S. Ocheretin) and the Big Five Inventory (BFI-2-S, K. Soto, O. John) were used. The results of the survey revealed the extent to which students mastered the skills necessary for studying in a digital environment and whether these skills influenced their academic success. The study also examined the effect of the digitalization of education on the quality of education and identified the most effective learning formats as reported by respondents. Multiple regression analyses identified personality traits (Big Five factors) that underlie students' attitudes towards the digitalization of education. The results can be used to individualize the educational process at universities when implementing various educational technologies.